Potency and efficacy of a low pathogenic H5N2 inactivated vaccine against challenge with a Malaysian H5N1 highly pathogenic avian influenza virus - Syed Hassan, Sharifah; M. Noor, Suriani; Mohamed, Maizan; Ong, G. H.; D., Azizah; K., Suzana; Omar, Abdul Rahman; Ideris, Aini (Veterinary Association Malaysia, 2013)
The potency and efficacy of an avian influenza (AI) H5N2 inactivated vaccine that was developed at Veterinary Research Institute, Ipoh was tested. The percentage sequence identity of the HA gene of the H5N2 vaccine virus to the challenge virus [A/chicken/Malaysia/5858/04 (H5N1)] was 88.2% by nucleotide and 90% by amino acid sequences similarities, respectively. As for the HAI segment, the nucleotide sequence similarities were 88.3 % and by amino acid sequence 87.7%.For potency testing, the heterologous killed H5N2 AI vaccine, formulated as an oil emulsion was administered only once subcutaneously in twenty five two-week old commercial broiler chickens. The HI antibodies were not detectable at week 1 post vaccination. The HI GMT attained was 30, 63, 200, 54 and 32 by week 2, 3, 4, 5, and 6 post vaccinations. Efficacy study was conducted on ten SPF chickens at week 3 post vaccination. 60% of the birds (6/10) with HI titres ≥ 64 - 128 survived the challenged. H5N1 challenge virus was reisolated from all the birds with HI titre ≤ 32 that died, and each of the birds that survived with HI titres of 64 and 128, from the oropharynx and cloaca at day 3 post challenge. This vaccine protected 60% of chickens against mortality and did not prevent shedding after challenged with a HPAI H5N1 virus.